Materials for pulpotomy in immature permanent teeth: a systematic review and meta-analysis - Yuan Chen; Xinlei Chen; Yali Zhang; Fangjie Zhou; Jiaxin Deng; Jing Zou; Yan Wang (BMC, 2019)
Abstract Background Pulpotomy is one of the most widely used methods in preserving vital pulp in teeth, which is of great significance in achieving continue root formation in immature permanent teeth suffering from dental caries or trauma. The aim of this meta-analysis and systemic review is to synthesize the available evidences to compare different pulpotomy dressing agents for pulpotomy treatment in immature permanent teeth. Methods Electronic databases including MEDLINE (via Pubmed), EMBASE, the Cochrane library (CENTRAL) and the clinicaltrials.gov database were searched. The references of all included articles or relevant reviews were cross-checked. Only randomized controlled trials (RCTs) comparing two or more pulp dressing agent in permanent teeth with open apex would be included. Also, the studies should have at least 6 months of follow-up, report clinical and radiographic success in detail and publish in English. Results Five RCTs were included for a systematic review, and all of them had a high risk of bias. There is little difference in success rate between mineral trioxide aggregate (MTA) and calcium hydroxide (CH) at 6-month follow-up (risk ratio (RR) 1; 95% confidence interval (CI) 0.94 to 1.06) and 12-month follow-up (RR 1.04; 95% CI 0.96 to 1.13). There is no difference between MTA versus platelet-rich fibrin and MTA versus calcium-enriched mixture (CEM). There is only weak evidence of increased success rate in using MTA and triple antibiotic paste (TAP) rather than abscess remedy. Conclusions Based on the present evidence, similar success rates with MTA were found between the dressing agents CH, CEM, RPF and TAP as pulpotomy-dressing agents in the treatment of immature permanent teeth. More high-quality RCTs are needed in this field in future studies.